Data for proteome analysis of Bacillus lehensis G1 in starch-containing medium - Ling, H. L. (Elsevier Inc., 2017)
Bacillus lehensis G1 is a cyclodextrin glucanotransferase (CGTase) producer, which can degrade starch into cyclodextrin. Here, we present the proteomics data of B. lehensis cultured in starch-containing medium, which is related to the article “Proteome-based identification of signal peptides for improved secretion of recombinant cyclomaltodextrin glucanotransferase in Escherichia coli” (Ling et. al, in press). This dataset was generated to better understand the secretion of proteins involved in starch utilization for bacterial sustained growth. A 2-DE proteomic technique was used and the proteins were tryptically digested followed by detection using MALDI-TOF/TOF. Proteins were classified into functional groups using the information available in SubtiList webserver (http://genolist.pasteur.fr/SubtiList/).